A retrospective, multicenter study of voriconazole trough concentrations and safety in patients with Child‐Pugh class C cirrhosis. (11th June 2018) - Wang, T.; Yan, M.; Tang, D.; Xue, L.; Zhang, T.; Dong, Y.; Zhu, L.; Wang, X.; Dong, Y.
Summary: What is known and objective: Voriconazole is a broad‐spectrum antifungal agent and is mainly metabolized by the liver, yet there have been no reports about voriconazole treatment in patients with Child‐Pugh class C cirrhosis. The objective of this study was to investigate the pharmacokinetic profile and safety of voriconazole treatment in this cohort of patients. Methods: A retrospective, multicenter study was performed in patients with Child‐Pugh class C cirrhosis who received a voriconazole maintenance dose of 100 mg twice daily (group A) or 200 mg daily (group B) orally or intravenously. All voriconazole C min were measured by high‐performance liquid chromatography, and voriconazole‐related adverse events were defined according to Common Terminology Criteria for Adverse Events. The relationship between voriconazole C min and adverse events was explored using logistic regression model. Results and discussion: A total of 51 voriconazole C min were monitored from 34 patients. The C min of voriconazole was 4.42 ± 2.08 and 5.42 ± 1.96 mg/L in groups A and B, respectively. The proportion of voriconazole C min over the upper limit of therapeutic level (5 mg/L) in groups A and B was 34.48% and 47.62%, respectively. Additionally, 23.5% (8/34) of patients exhibited signs of voriconazole‐related adverse events, and 87.5% (7/8) of adverse events occurred within the first week after voriconazole treatment. Logistic regression model showed that there was a positive correlation between voriconazole C min and the incidence of adverse reactions. Voriconazole C min value of 4.5 mg/L was associated with a 20% probability of adverse events. What is new and conclusion: The voriconazole maintenance dose of 100 mg twice daily or 200 mg daily orally or intravenously may be inappropriate in patients with Child‐Pugh class C cirrhosis because of the higher voriconazole C min and higher incidence of adverse events. Monitoring voriconazole C min earlier is extremely important to prevent the occurrence of voriconazole‐related adverse reactions. Abstract : We investigated the pharmacokinetic characteristics and safety of voriconazole treatment in patients with Child‐Pugh class C cirrhosis. It demonstrated that the two regimens of halved maintenance dose were inappropriate towards these patients who had a higher voriconazole trough concentration and incidence of adverse events.